Pendekatan Anestesi pada Bedah Tulang Belakang - Ghozali, Imam; Hamdi, Tasrif; Ayu Assyifa Hamka Dinata (Medula, 2024)
Spinal anesthesia is performed by injecting local anesthetic into the cerebro-spinal fluid. An anesthesiologist's adequate knowledge of anatomy, physiology, and pharmacology will make anesthesia safe and satisfactory for the patient, surgeon, and anesthesiologist. Spinal anesthesia is now often used in spinal surgery. The advantages of using this technique are a lower postoperative pain scale, minimizing the effects of postoperative nausea and vomiting, a shorter procedure, and high patient satisfaction. The first case was Mr S aged 55 years with a diagnosis of low back pain and compression of lumbar vertebra 4, lumbar 5 and sacrum 1 undergoing laminectomy, decompression and biopsy. The second case, Mrs. NH, aged 46 years, was diagnosed with ASIA 3 spinal cord syndrome and compression fracture of the T 10-11 vertebra, undergoing thoracic fusion and laminectomy surgery. The third case, Mrs. H, aged 53 years, was diagnosed with T10-11 tuberculous spondylitis who underwent laminectomy, thoracolumbar fusion and biopsy. Anesthesia for the first case (Mr. S) and the second case (Mrs. NH) used Single-Shot Anestesi Spinal Segmental Thoracic atau Thoracic Spinal Anesthesia (TSA). Meanwhile, the anesthesia for the third case (Mrs H) used the Two Stabbing Techniques.